ANALISIS PERTUMBUHAN TRANSAKSI SIMPAN PINJAM KKOPERASI SEBELUM DAN SELAMA PSBB STUDI KASUS PADA KOPERASI KARUNIKA - Erman Sutandar; Slamet Soesanto (Institut Teknologi dan Bisnis Swadharma, 2020)
The basis of cooperative activities is cooperation which is considered as a way to solve various problems faced by each member. Moreover, during this PSBB period, there were many people whose income was reduced. Therefore, it is appropriate for cooperatives to be important in the economic system of a country in addition to other economic sectors. In January 2020 the number of borrowers at the Karunika cooperative was 51 with a loan amount of Rp. 1,114,980,161, -. And in February 2020 the number of borrowers decreased to 41 people with a loan amount of Rp. 524,916,840, - decreased by 52.9% from January. However, at the end of the first quarter in March 2020 the number of borrowers had jumped dramatically to 97 people with a loan amount of Rp. 1,983,962,076, - increased by 277% from the previous month. Even though it does not have a significant financial contribution to increasing SHU, the Koperasi Karunika savings and loans business has fulfilled the purpose of establishing this cooperative, namely the welfare of its members. This can be seen from year to year there is an increase in the number of loans and the amount of funds lent